2022
DOI: 10.1002/cncr.34155
|View full text |Cite
|
Sign up to set email alerts
|

De‐escalation of five‐year adjuvant endocrine therapy in patients with estrogen receptor‐low positive (immunohistochemistry staining 1%‐10%) breast cancer: Propensity‐matched analysis from a prospectively maintained cohort

Abstract: BACKGROUND:The standard 5 years of endocrine therapy has demonstrated additional benefits compared with short-term (2-3 years) treatment in patients with estrogen receptor (ER)-positive breast cancer; however, data specific to ER-low positive breast cancer (1%-10% by immunohistochemistry) are limited, and it is unclear whether long-term treatment is still necessary for this subgroup. METHODS:The authors used the prospectively maintained Breast Surgery Database of Fudan University Shanghai Cancer Center for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In the present study, ER low cases constituted 2% (46/2,309) of all IBC cases and 2.8% (46/1,666) of ER-positive IBC cases, which is consistent with previous studies that reported ER low cases accounted for 2%–5.1% of all IBC and 2.5%–7.4% of ER-positive IBC cases [ 6 7 9 13 14 15 ]. Some studies [ 9 13 ] have defined ER low as 1%–9% positive staining instead of 1%–10% (the ASCO/CAP definition).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, ER low cases constituted 2% (46/2,309) of all IBC cases and 2.8% (46/1,666) of ER-positive IBC cases, which is consistent with previous studies that reported ER low cases accounted for 2%–5.1% of all IBC and 2.5%–7.4% of ER-positive IBC cases [ 6 7 9 13 14 15 ]. Some studies [ 9 13 ] have defined ER low as 1%–9% positive staining instead of 1%–10% (the ASCO/CAP definition).…”
Section: Discussionsupporting
confidence: 93%
“…These results support the notion that hormone therapy has limited benefits for ER low breast cancer patients. Cai et al [ 15 ] recently reported that short-term endocrine therapy for 2–3 years might be an alternative for patients with ER low breast cancer instead of standard 5 years of treatment because there was no significant difference in DFS between the 2 groups. We did not observe differences in DFS of patients with ER low according to hormone therapy, although the comparison was made with a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the 5-year survival outcome in traditional antitumor modalities has clinical progress, the mortality in patients with advanced tumors remained undiminished owing to metastasis and recurrence (Zhang et al, 2016;Zhang et al, 2017;Zhang et al, 2018a;Zhang et al, 2020a;Cai et al, 2022). Hypoxic tumor microenvironment (TME) is gradually recognized as an essential factor in tumor progression, especially in multidrug resistance, radiosensitivity, immunologic escape, and metastasis (Jiang et al, 2020;Jin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other limitations include the lack of quantification of progesterone receptor (PR) status. Although the study includes positive or negative PR status (see their Table 1 16 ), quantification was not reported, and PR status was not included in propensity matching although PR expression is a known prognostic variable. 3,17 The study does not address the question of whether PR status influences the decision for duration of endocrine therapy.…”
mentioning
confidence: 99%
“…In this issue of cancer, Cai et al 16 take an important look at the topic of endocrine therapy for ER‐low tumors. Theirs was a single‐center, prospective study of 634 eligible patients using propensity‐matched analysis to compare DFS in patients with ER‐low breast cancer who received no endocrine therapy, 2 to 3 years of endocrine therapy, or 5 years of endocrine therapy.…”
mentioning
confidence: 99%